Physiological response mechanism and stress resistance characteristics of four garden plants under heavy metal stress - Li, Ning; Lu, Ning; Zhang, Junye; Yu, Yuanchun (Frontiers in Environmental Science, 2025)
To better explore the resistance of garden plants to heavy metals and to achieve the ecological remediation of garden plants in heavy metal contaminated soils, the study analyzed their resistance under heavy metals and combined with ameliorated soils for experimental design. The soil and plant analyzer development values of rhododendrons and heather were reduced by more than 15% when treated with heavy metals, and the malondialdehyde of gardenia was increased by 6.42% on Zinc (Zn). The gardenia plant had significant Zn and Cadmium (Cd) accumulation ability, the enrichment coefficient of rhododendron root system under Copper (Cu) was 6.38, and the transfer coefficient of Cu metal of weigela was about 2.0. Compared with the control, the difference of proline content of rhododendron and gardenia under the treatment of the improved soil was more than 9 times. Meanwhile, the reduction trend of Pb, Zn, and Cu in the cultivated soil of cuckoo with diethylenetriaminepentaacetic acid applied was 28% higher than that of the blank control, which indicated that gardenia had a better effect of diethylenetriaminepentaacetic acid-Cu applied. The research results show that the physiological response and accumulation of garden plants to heavy metals demonstrate their tolerance to heavy metals, and the addition of stabilizers in heavy metal contaminated soil is feasible. This research content can promote the excavation of garden plants with high tolerance potential, and has reference technical value for the restoration of ecological landscapes in mining areas.